Increased levels of circulating oxidized mitochondrial DNA contribute to chronic inflammation in metabolic syndrome, and MitoQ-based antioxidant therapy alleviates this DNA-induced inflammation. (15th January 2023) - Ye, Wei; Wen, Chaowei; Zeng, Aibing; Hu, Xingzhong
Abstract: Here, the aim was to investigate the role of circulating oxidized mitochondrial DNA (ox-mtDNA) in metabolic syndrome (MetS)-associated chronic inflammation and evaluate the effect of Mito-Quinone (MitoQ)-based antioxidant therapy on inflammation. A total of 112 MetS patients and 111 healthy control individuals (HCs) were recruited. Peripheral blood was collected, and mononuclear cells (PBMCs) were separated. In a preclinical study, MitoQ, a mitochondrial-targeted antioxidant, was administered to Sprague-Dawley (SD) rats fed a high-fat diet (HFD). In vitro, H2 O2 - or MitoQ-treated HUVECs served as the oxidative or antioxidative cell models to detect the cell-free ox-mtDNA level. Plasma or cell-free ox-mtDNA levels were measured by qPCR. Additionally, THP-1 cells were incubated with plasma cell-free DNA (cfDNA) from MetS patients and HCs or cell-free ox-mtDNA to detect TLR9-NF-κB pathway activation. Plasma ox-mtDNA levels and TLR9 expression levels in PBMCs were increased in MetS patients. In vivo, HFD-fed rats showed elevated plasma ox-mtDNA and TLR9 expression levels in cardiac-residing immune cells, but MitoQ administration attenuated these increases. In vitro, a significant lower level of cell-free ox-mtDNA was detected in MitoQ-treated cells, compared with H2 O2 -treated cells. Coincubation of plasma cfDNA from MetS patients or cell-free ox-mtDNA and THP-1 cells increased TLR9-NF-κB p65 expression, and promoted IL-1β, IL-6 and IL-8 secretion in THP-1 cells. In conclusion, increased circulating ox-mtDNA contributes to chronic inflammation in MetS by activating the TLR9-NF-κB pathway. MitoQ-based antioxidant therapy effectively alleviates inflammation by reducing ox-mtDNA release. Graphical abstract: Image 1 Highlights: Circulating oxidized mtDNA levels are increased in metabolic syndrome patients. Oxidized mtDNA triggers inflammation by activating TLR9. MitoQ-based antioxidant therapy alleviates inflammation by reducing the release of oxidized mtDNA.